Solidarity with the Fulfillment of Women's Political Representations in Indramayu Regency - Herpita Wahyuni; Zuly Qodir; Danang Eko Prastya; Bilveer Singh (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
In this study, it can be seen that the role of fellow women in supporting women to be involved in the political realm is a factor that can increase the value of women in women's involvement in politics in the Indramayu Regency. This research is descriptive qualitative research by describing the findings from various literature and previous studies in answering the research results. The survey results show that solidarity among women in increasing women's political participation in Indramayu Regency comes from a sense of unity among women who are members of a young women's organization called Fatayat Nahdlatul Ulama in fighting for women's rights. Friendship among women in Indramayu Regency is a form of strength between women who support politics by empowering women in the Indramayu Regency. Mutual trust among women in Indramayu Regency is an essential point in women's courage to join the world of politics. The interests that are fought for by women in Indramayu Regency are to advance women in various fields, including education, health, economy, social welfare, legal awareness, political education, and women's empowerment in Indramayu Regency. Empowering women can develop their potential and change a healthier political climate, and prepare women who are strong in politics, culture, economy, and education. This research limit is only looking at women's solidarity in supporting women's representation in politics in Indramayu Regency.